Increased levels of promutagenic etheno-dna adducts in colonic polyps of FAP patients - Schmid, Karen U.; Nair, Jagadeesan; Bartsch, Helmut (International journal of cancer, 2000)
Nonsteroidal anti-inflammatory drugs (NSAIDs) can regress adenomas in patients with familial adenomatous polyposis (FAP), and the mechanism involves inhibition of cyclooxygenases (COX). Reactive intermediates formed during the arachidonic acid cascade, notably by COX-2, which is upregulated in polyps of FAP patients, may promote various stages of the polyp → adenoma → carcinoma sequence. Etheno-DNA adducts can be derived from reactive intermediates generated during arachidonic acid metabolism and lipid peroxidation. We tested this hypothesis in colonic polyps from FAP patients and colorectal tissue from cancer patients to see whether increased formation of etheno-DNA adducts occurs. Using an ultra-sensitive and specific immunoaffinity/32P-postlabelling method, 1,N6-ethenodeoxyadenosine (ϵdA) and 3,N4-ethenodeoxycytidine (ϵdC) were quantitated in epithelial cell DNA from asymptomatic colon, FAP polyps and colon tumor tissues. Mean adduct levels in FAP polyps were 65 ϵdA/109 and 59 ϵdC/109 parent nucleotides, being 2 to 3 times higher than in unaffected colon tissue (p < 0.02 for ϵdA; p < 0.05 for ϵdC). Adduct levels in colonic epithelia decreased in the order: FAP polyps > tumor-adjacent tissue > tumor, normal and tumor-distal tissue. Based on this study, requiring confirmation in a larger number of patients and in experimental models, we have demonstrated the formation of promutagenic etheno-DNA adducts in adenomatous polyps of FAP patients that may contribute to genetic instability and cancer progression.